Effect of five key factors on the implementation of core banking system: (Case study: Bank of Industry and Mining) (International Journal of Scientific Research and Management (IJSRM), 2018)
The purpose of this study was to investigate and analyze the key factors affecting the implementation of the core banking system in the Bank of Industry and Mine. The researcher has tested the hypotheses by using the method of applied research, using correlation type and using the standard questionnaire. The questions from the managers and experts involved in the implementation project of 150 people have been questioned by a sample of 107 people and using the Morgan formula. In this research, key factors influencing the success of core banking systems implementation were identified, among which were five senior management support, the best project management method, business process reengineering, final user training, and vendor support. The main influential variables are selected from the research literature and their effect on the implementation of the core banking system has been analyzed. The results of the research indicate that senior management support and best project management methods and end user training have had the greatest impact on the success of the core banking system. [1] CBS